The effect of brexpiprazole (OPC-34712) and aripiprazole in adult patients with acute schizophrenia: results from a randomized, exploratory study. (July 2016) - Citrome, Leslie; Ota, Ai; Nagamizu, Kazuhiro; Perry, Pamela; Weiller, Emmanuelle; Baker, Ross A.
Abstract : The aim of this study was to explore the effects of brexpiprazole and aripiprazole on efficacy, cognitive functioning, and safety in patients with acute schizophrenia. Patients who would benefit from hospitalization/continued hospitalization for acute relapse of schizophrenia were enrolled and randomized (2 : 1) to target doses of open-label brexpiprazole 3 mg/day or aripiprazole 15 mg/day for 6 weeks. Outcomes included change from baseline to week 6 in the Positive and Negative Syndrome Scale total score, Barratt Impulsiveness Scale 11-item score, and Cogstate computerized cognitive test battery scores. Patients treated with brexpiprazole ( n =64) or aripiprazole ( n =33) showed reductions in symptoms of schizophrenia as assessed by Positive and Negative Syndrome Scale total score (−22.9 and −19.4, respectively). A modest reduction in impulsivity was observed with brexpiprazole, but not aripiprazole (mean change in the Barratt Impulsiveness Scale 11-item total score: −2.7 and 0.1, respectively). No change in Cogstate scores was observed for either treatment. Brexpiprazole was well tolerated and the incidence of akathisia was lower in patients treated with brexpiprazole (9.4%) than aripiprazole (21.2%). Clinically relevant improvements in psychopathology were observed in patients with acute schizophrenia treated with brexpiprazole or aripiprazole. Brexpiprazole was well tolerated, with a lower incidence of akathisia than aripiprazole. Abstract : Supplemental Digital Content is available in the text.